Effect of Xingnao Kaiqiao Acupuncture combined with EEG Biomimetic Electrical Stimulation on Evoked Potential of Patients with Persistent Vegetative State - Lixia DENG; Jiquan LIU; Liangxiang ZHANG; Xiao LV; Xing CHEN; Yigang FENG; Yingying NI (康复学报)
Objective:To observe the effect of Xingnao Kaiqiao acupuncture combined with EEG biomimetic electrical stimulation on brainstem auditory evoked potential (BEAP) and somatosensory evoked potential (SEP) in patients with persistent vegetative state (PVS).Methods:A total of ninety patients with PVS treated in the PVS awareness center of Guangdong 999 Brain hospital were randomly divided into Acupuncture group, Bionic electricity group and Combined group, with thirty cases in each group. All groups were given routine treatment, including basic management, hyperbaric oxygen therapy and drug treatment etc. In addition, the Acupuncture group received Xingnao Kaiqiao acupuncture, the refreshement treatment, at which the main acupoints were Shuigou, bilateral Neiguan, bilateral Sanyinjiao, and the auxiliary acupoints were Jiquan, Chize and Weizhong acupoints, once a day, the Bionic electricity group received the treatment of EEG bionic electrical stimulation, the main electrode were placed at GB 12 and BL 10, each treatment was for a continuous 99 min followed by a rest of 30 min, followed by another 99 min, once a day, the Combined group received Xingnao Kaiqiao acupuncture combined with EEG bionic electrical stimulation, once a day. Three groups were treated continuously for thirty days. On the day before treatment and the day after treatment, the consciousness state of the three groups was assessed by the revised coma recovery scale (CRS-R), and the grades of BAEP, SEP and the changes of latency and interval of each wave on the affected side were monitored by electromyographic evoked potential.Results:Before treatment, there was no significant difference of the CRS-R scores, the grades of SEP and BAEP, the latency of I, V, P15, N20, P38 wave and I-V wave interval in three groups (P>0.05). Compared with before treatment, the CRS-R scores after treatment were significantly higher, the grades of SEP and BAEP after treatment were significantly lower, the latency of I, V, P15, N20, P38 wave and I-V wave interval were significantly shorter, with statistically significant differences (P<0.05). Compared with the Acupuncture group and the Bionic electric group after treatment, the CRS-R scores of the Combined group were higher, the grades of SEP and BAEP in the Combined group were lower, with statistically significant differences (P<0.05). The latency of I, V, P15, N20, P38 wave and I-V wave interval in the Combined group after treatment were significantly shorter than those of the Acupuncture group and the Bionic electricity group, with statistically significant differences (P<0.05).Conclusion:Xingnao Kaiqiao acupuncture combined with EEG biomimetic electrical stimulation is helpful to promote the consciousness recovery of PVS patients, improving the clinical effect of awakening, and improve SEP and BAEP in patients with persistent vegetative state.